Tindakan Penyalahgunaan Keadaan (Misbruik Van Obstandigheden) dalam Penyaluran Tenaga Kerja (Studi Kasus Penyaluran Tenaga Kerja di Kecamatan Doro) - Izza, Siti Zuhrotul; Diniyanto, Ayon; M. Asro (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
This study aims to find the existence of abuse of circumstances in the placement of labor and the legal consequences that occur from the existence of abuse of circumstances in the placement of labor. By using empirical legal methods and through the approach of legislation, conceptual and case analysis. This study resulted in that there were several placements of labor as household assistants. The agreement from one of the placement places was not in accordance with the agreement in general, namely by not fulfilling one of the valid conditions of the agreement. In addition, the placement of labor that existed did not meet the legal regulations applicable to a place of placement of labor, that the placement place had not been registered as an official institution for placement of labor and from this it could cause several legal consequences, including the agreement that was made could be canceled, not getting a way to resolve it if a problem occurred through legal channels, and so on. This study contributes to the need for a valid agreement in accordance with the norms of the contract in accordance with positive law in Indonesia.